APPLICATION OF WAHDATUL ULUM (INTEGRATION OF SCIENCE) IN EDUCATION AND LEARNING - Ramadhani, Three Wulan (Tadrib: Jurnal Pendidikan Agama Islam, 2023)
The knowledge that originated from the Muslims was adopted by Western people and applied by them in their country resulting in Western people experiencing the development of knowledge. The development of science in the West has been rejected by the teachings of the church because the science that developed is not in accordance with the teachings of the church which resulted in many Western scientists being killed. The incident gave rise to a scientific dichotomy, namely the division between general knowledge and religious knowledge. The use of the methodology in this study is a descriptive type of research because there is a goal to get answers that are associated with opinions and responses so that qualitative (descriptive) research must be carried out. The research method used in data collection is literature-based data collection aimed at processing data and information from written documents, namely books related to the research title. The results of the discussion can be described as follows: The influence of the scientific dichotomy by Western people affects civilization, especially in the field of education. Many educators do not know or do not want to know about this knowledge sharing. Until finally the dichotomy of science is believed to be different when in fact all knowledge only comes from one, namely Allah SWTt. Therefore, to eliminate this influence, a new concept is needed, namely Wahdatul Ulum. This concept is the opposite of the scientific dichotomy. In the education system, this concept is applied using a transdisciplinary concept in developing curriculum and learning strategies. Curriculum preparation plans that are implemented before the learning process takes place, while learning is an educator's activity in selecting and determining methods and media in the learning process.